Landsat TM and ETM+ derived snowline altitudes in the Cordillera Huayhuash and Cordillera Raura, Peru, 1986–2005 - McFadden, E. M.; Ramage, J.; Rodbell, D. T. (The Cryosphere, 2011)
The Cordilleras Huayhuash and Raura are remote glacierized ranges in the Andes Mountains of Peru. A robust assessment of modern glacier change is important for understanding how regional change affects Andean communities, and for placing paleo-glaciers in a context relative to modern glaciation and climate. Snowline altitudes (SLAs) derived from satellite imagery are used as a proxy for modern (1986–2005) local climate change in a key transition zone in the Andes. Clear sky, dry season Landsat Thematic Mapper (TM) and Enhanced Thematic Mapper (ETM+) satellite images from 1986–2005 were used to identify snowline positions, and their altitude ranges were extracted from an Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) digital elevation model (DEM). Based on satellite records from 31 glaciers, average snowline altitudes (SLAs), an approximation for the equilibrium line altitude (ELA), for the Cordillera Huayhuash (13 glaciers) and Cordillera Raura (18 glaciers) from 1986–2005 were 5051 m a.s.l. from 1986–2005 and 5006 m a.s.l. from 1986–2002, respectively. During the same time period, the Cordillera Huayhuash SLA experienced no significant change while the Cordillera Raura SLA rose significantly from 4947 m a.s.l. to 5044 m a.s.l.